(untitled) (Annals of Medical Research, 2022)
Aim: Pregnancy is considered a vulnerable period for women regarding increased risk of respiratory tract infections, altered immunity, and metabolic changes in their bodies. COVID-19 pandemic also possesses a significant risk on pregnant women, but the data on the disease course is insufficient. Therefore, this study aimed to evaluate the maternal and perinatal outcomes in pregnant women diagnosed with COVID-19. Materials and Methods: This cross-sectional study retrospectively evaluated the hospital records of pregnant women admitted to the Obstetrics and Gynecology Department of 19 MayısUniversity Hospital between 01/04/2020 to 30/12/2021 regarding gestational week at birth, basal gestational, and labor characteristics, delivery complications, and perinatal and maternal COVID-19 outcomes. Results: Analyses of the data of 98 patients revealed that the median age of the mothers was 30 years; 26.5% were primigravid, 43.9% were nulliparous, 29.6% were primiparous, and 3 had twin pregnancies. In addition, 52% of the births were preterm, 88% were cephalic presentation, and 95.9% were cesarean deliveries. The most common delivery complications were acute fetal distress (51%), preterm premature rupture of membranes (50%), and neonatal asphyxia (49%). Gestational characteristics were similar between treatment groups for COVID-19, but patients admitted to intensive care unit and applied mechanical ventilation (11.2%) had significantly more preterm births, and perinatal complications including acute fetal distress (p=0.030), PPROM (p<0.001), neonatal asphyxia (p=0.021), and lower APGAR scores (p=0.002). Conclusion: COVID-19 is a significant risk factor for pregnant women. This study showed that COVID-19 and pregnancy might induce adverse effects on each other. The data provided here will contribute to the growing epidemiological and clinical evidence on the interactions between COVID-19 and pregnancies.